Living arrangements of poor older Malaysians by sex-disaggregation - Zainalaludin, Zumilah; Saidi, Norehan (Faculty of Medicine and Health Sciences, 2022)
This paper reports on living arrangements predict poor older Malaysians by sex disaggregation. The respondents in this paper are 60 years old and above in 2016, to a total n=2467 (50.8% men, and 49.2% female) from 91 districts in Malaysia. The majority poor male (64.92%), and female (60.3%) respondents are living with children. Three types of significant (p<0.05) living arrangements predict poor male respondents are living with-spouse-only (odd=8.357) with children (odd=5.141), and with relative (odd=2.514). Three types of significant (p<0.05) living arrangements predict poor female respondents are living with-spouse-only (odd=53.333) with children (odd=8.69), and with relative (odd=3.257).